1999
DOI: 10.1104/pp.120.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Nodule-Inducing Activity of Synthetic Sinorhizobium meliloti Nodulation Factors and Related Lipo-Chitooligosaccharides on Alfalfa.Importance of the Acyl Chain Structure1

Abstract: Sinorhizobium meliloti nodulation factors (NFs) elicit a number of symbiotic responses in alfalfa (؊7 M. The optimal chain length was C16, with the C16-LCO being more than 10-fold more active than the C12-and C18-LCOs. Unsaturations were important, and the diunsaturated 2E,9Z LCO was more active than the monounsaturated LCOs. We discuss different hypotheses for the role of the acyl chain in NF perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…As an alternative, we have used cell cultures to characterize NFBSs, as they represent an abundant source of plant material and have been used from a number of species for the biochemical characterization of many putative receptors (22,23). By using M. varia cell cultures (9), a high-specific activity ligand (8) and a range of pure, modified, and differentially substituted LCOs (13,14,18,24), we have characterized a high-affinity, protease-sensitive binding site for Nod factors (NFBS2) that exhibits a K d of 4 nM for the major Nod factor of R. meliloti, the symbiont of Medicago.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, we have used cell cultures to characterize NFBSs, as they represent an abundant source of plant material and have been used from a number of species for the biochemical characterization of many putative receptors (22,23). By using M. varia cell cultures (9), a high-specific activity ligand (8) and a range of pure, modified, and differentially substituted LCOs (13,14,18,24), we have characterized a high-affinity, protease-sensitive binding site for Nod factors (NFBS2) that exhibits a K d of 4 nM for the major Nod factor of R. meliloti, the symbiont of Medicago.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups further proposed alternative strategies for the synthesis of the NodSm factor [12][13][14] or the Nod factors produced by Bradyrhizobium japonicum, the symbiont of soybean [15]. The procedure established by Tailler et al [13] enabled the synthesis of a series of tetrameric sulfated LCOs differing for the structure of the fatty acid (length, degree and position of unsaturations) to perform structure-function studies [16]. Later on, large scale production of LCOs was achieved by chemo-enzymatic synthesis [17,18].…”
Section: Chemical Synthesis Of Nod Factorsmentioning
confidence: 98%
“…While the presence of the sulfate group is essential for all biological responses, the structure of the fatty acid also plays an important role. By using synthetic LCOs differing by the length of the fatty acid (C8, C12, C16, C18) and the number or the position of the unsaturations, it was shown that the optimal chain length was C16 and LCO-IV(S,C16:2Δ2, 9) was more active than LCO-IV(S,C16:1Δ9) [16]. The role of the different substitutions on the oligochitin backbone or the structure of the lipid chain in Nod factor recognition was then examined by conformational studies of natural Nod factors and synthetic analogs, notably benzamide analogs, designed to mimic the geometry of the conjugated double bond in natural NodSm factors [27].…”
Section: Nod Factor Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…7;8 Each rhizobial strain produces a wide range of structurally related LCOs that may be needed at different stages of the symbiosis and to complement one another. [9][10][11] To circumvent the problem caused by the small amount of LCOs produced, genetically modified LCO over-producing strains have been used since the first study of LCO structures. 4 The wild-type strains produce similar LCOs to the over-producing strains.…”
Section: Introductionmentioning
confidence: 99%